KGB Agents: their Types, Functions and Objectives - Burinskaitė, Kristina (Genocidas ir rezistencija, 2019)
KGB agents are one of its pillars and sources of power since on the basis of the information they provided, the operative work was organized, which ensured that the atmosphere of fear and obedience pervade society. The goal of this research is to name and define the types of agents, the tasks they had to carry out, the goals to be achieved as well as in what segments of the population they were most active. The definition of an agent in KGB documents is a Soviet citizen, a foreign country national (subordinate) or an individual who has no citizenship, who collaborated secretly with the KGB organs and fulfilled its tasks ensuring internal security in the USSR. The committee’s apparatus consisted of agents, residents, owners of apartments for secret meetings, and owners of conspiracy apartments who were not on the staff of the agency. KGB secret agents are divided into certain types by the nature of their activities and the tasks they were to carry out. Agents infiltrated into the clergy controlled the Church and seminaries’ activities, attempted to exert influence on anti-Soviet priests as well as to form a positive position of the Vatican and the community of the devout that was in favour of the Soviet regime. Among the émigré communities their goal was to harm the organisations of the diaspora and discredit the cause of Lithuania’s liberation for which they fought. The objective of the agents who were in charge of monitoring resistance activities was to uncover anti-Soviet schemes, especially the ways and organizers of samizdat. They aimed to influence people so that they avoided resistance, and those who got involved would abandon it. Agents using various instruments such as spreading disinformation about individuals, compromising them, trying to “reeducate” them took efforts to discredit non-conformists in the eyes of the public. The role of agents was particularly important for explaining the activities of resistance both in Lithuania and the West. After 1953, requirements for agents were more demanding than before. However, constant search for secret collaborators demonstrates that the work was complicated and the results could not satisfy the KGB although separate individuals suffered harm.